1H-Pyrrole, Furan, and Thiophene Molecule Corrosion Inhibitor Behaviors - Ahmed, Lana; Omer, Rebaz (Niyazi BULUT, 2021)
The corrosion inhibitor behaviors of the molecules 1H-Pyrrole, Furan, and Thiophene were examined using the computational quantum method. The density functional theory (DFT) was applied to the 6-31G (d, p) basis set, parameters such as the energy of the highest occupied molecular orbital (EHOMO), the energy of the lowest unoccupied molecular orbital (ELUMO), the energy difference (?E) and the dipole moment (?) were calculated. These parameters are correlated with the corrosion effects of organic compounds that are mainly investigated in molecular geometry and electronics. Besides, the chemical hardness (?), softness (?), electronegativity (?) have been determined. The transmitted electrons fraction (?N), have been determined between cupper surface and the 1H-Pyrrol, Furan and the Thiophene molecule. The parameters that have a direct relation with inhibition efficiency are described. According to the obtained results, it can be said that 1H-Pyrrole inhibitor provides a good inhibition activity which can be used as a good anti-corrosion agent. There is an inverse relationship between the transmitted electrons fraction (?N) and electronegativity (?) of inhibitor. The behavior of the corrosion inhibitor can therefore be predicted without an experimental analysis.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik